Enhancing Māori food security using traditional kai. (September 2015) - McKerchar, Christina; Bowers, Sharron; Heta, Craig; Signal, Louise; Matoe, Leonie
Issue: Lack of food security is one of the major nutrition issues facing Māori today. Loss of traditional kai (food) gathering places and practices following colonisation and urbanisation has impacted negatively on food security for Māori. This paper explores the role of Māori in enhancing Māori food security through revitalising traditional kai . Methods: A narrative literature review of peer reviewed and grey literature on revitalising traditional kai for Māori was conducted. The focus was on two areas: increasing the availability of traditional kai to Māori households (such as through replenishing fish stocks, and gardening projects) and increasing the financial means available to Māori households to purchase food (by economic development of traditional kai industries and employment creation). Results: A range of activities to improve food security for Māori by revitalising traditional kai was identified in the literature. Māori are now significant players in New Zealand's fishing industry, and are developing their horticultural resources. Gardening initiatives have also grown considerably in Māori communities. Enabling factors included: the return of traditional kai resources by the Crown, and successful pursuit by Māori of the legal rights to develop them; development of Māori models of governance; government policy around Māori economic development and healthy eating; and Māori leadership on the issue. Barriers to revitalising traditional kai that remain to be addressed include: tensions between Government and Māori goals and models of resource management; economic pressures resulting in severely depleted fishing stocks; and pollution of marine and freshwater fish. Conclusion: Revitalising traditional kai has considerable potential to improve food security for Māori, both directly in terms of food supply and by providing income, and warrants policy and practical support. These findings have implications for other indigenous cultures who are struggling to be food secure.